2021
DOI: 10.3390/ijms22179299
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Fracture Healing: Comparison between Diaphysis and Metaphysis in the Mouse Long Bone

Abstract: The process of fracture healing varies depending upon internal and external factors, such as the fracture site, mode of injury, and mechanical environment. This review focuses on site-specific fracture healing, particularly diaphyseal and metaphyseal healing in mouse long bones. Diaphyseal fractures heal by forming the periosteal and medullary callus, whereas metaphyseal fractures heal by forming the medullary callus. Bone healing in ovariectomized mice is accompanied by a decrease in the medullary callus form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 127 publications
0
6
0
Order By: Relevance
“…MCP-1 and TNF-α have been shown to do (23,24). The inflammatory phase of bone healing itself has been described to be limited, shorter and to terminate earlier in metaphyseal than diaphyseal fractures in animal models (22). This might explain our results in two ways, as they might be due to a similarly limited inflammatory phase in human fractures, as well as the fact that the inflammation might have been abrogated by the time samples were taken.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…MCP-1 and TNF-α have been shown to do (23,24). The inflammatory phase of bone healing itself has been described to be limited, shorter and to terminate earlier in metaphyseal than diaphyseal fractures in animal models (22). This might explain our results in two ways, as they might be due to a similarly limited inflammatory phase in human fractures, as well as the fact that the inflammation might have been abrogated by the time samples were taken.…”
Section: Discussionmentioning
confidence: 69%
“…In contrast, inflammatory markers are "silenced" in patients with metaphyseal fractures. These observed differences between metaphyseal and diaphyseal fractures might be a result of their different mechanisms of MSC recruitment (22). As the metaphyseal region has more mesenchymal progenitors than the diaphyseal region, it might case that diaphyseal healing requires more pronounced cytokine signaling in order to regulate MSC recruitment and proliferation in the periosteum, as e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the release rates of Exos in 3.33%HB‐PEGDA@1.33%SH‐HA group reached nearly 80% (hyaluronidase) and 90% (H 2 O 2 ), respectively. Since the typical bone healing time for mice is ≈21–42 days, [ 27 ] 3.33%HB‐PEGDA@1.33%SH‐HA group was chosen for further experiments to ensure that HMPs can exert their maximum effect during the healing period. Interestingly, in PBS solution, minimal release of Exos was detected (Figure 3C Figure S9C,D, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…This emphasizes how vulnerable and concise the process of fracture healing is in rats with a depleted estrogen reservoir. Kolios et al reported that estrogen improves metaphyseal healing via an increase in the medullary callus formation in OVX rats [ 11 , 16 , 37 ]. In these experiments, OVX rats had a significant amount of cancellous bone in the metaphysis due to the oral-supplemented estrogen over a 10-week period before the injury.…”
Section: Discussionmentioning
confidence: 99%
“…Piezoelectric osteotomy generates micro-vibrations. Those allow for bone cutting, although the surrounding tissue, including the underlying soft and neurovascular tissue, is not damaged based upon the mechanical effect of ultrasound [ 37 , 38 , 39 , 40 ]. Specific to a piezoelectric osteotomy is the cavitation phenomenon.…”
Section: Discussionmentioning
confidence: 99%